Pengaruh Motivasi Kerja Terhadap Kinerja Karawan Dengan Motivasi Islam Sebagai Variabel Moderasi - Ningtyas, Nurcahyati Dwi Ayu; Asfiah, Nurul; Rifa’i, Mochamad Novi (Falah: Jurnal Ekonomi Syariah, 2018)
This study aims to determine the effect of work motivation on employee performance with Islamic motivation as a moderating variable at the Ayam Bakar Wong Solo Restaurant, Malang Branch. This study uses a quantitative approach with the object of research at the Ayam Bakar Wong Solo Restaurant, Malang Branch. The selection of the company was because the Ayam Bakar Wong Solo Restaurant still existed and developed rapidly until now, behind the success there must be quality human resources who play an important role in developing it. The method used in this study with interviews and questionnaires. Using Data Analysis Scale and Moderation Analysis Range (MRA). The results of this study indicate that work motivation has a significant effect on employee performance. Islamic motivation has a significant effect on employee performance and Islamic motivation moderates the influence of work motivation on employee performance but is not significant. The conclusion in this study work motivation still affects employee performance without the motivation of Islam as a moderating variable.